Manganese is an additional cation that enhances colonial phase variation of Vibrio vulnificus. Issue 5 (7th August 2015) - Kaluskar, Zelam M.; Garrison‐Schilling, Katherine L.; McCarter, Kevin S.; Lambert, Bliss; Simar, Shelby R.; Pettis, Gregg S.
Summary V ibrio vulnificus, an inhabitant of marine and estuarine environments around the world, is the leading cause of reported seafood‐related deaths in the United States. Disease is caused by opaque colony‐forming strains that produce capsular polysaccharide, loss of which results in an unencapsulated translucent phenotype with diminished virulence potential. Rugose is a third phenotypic variant of V. vulnificus, and produces a separate exopolysaccharide that results in a dry, wrinkled appearance and the ability to form profuse biofilms. Phase variation among these three phenotypes is influenced by several environmental factors, including the presence of calcium in the medium (Garrison‐Schilling et al.). In this study, we have identified a second cation, manganese, which substantially increases the propensity of opaque V. vulnificus strains to switch to translucent or rugose phenotypes. In comparative studies, manganese and calcium promoted switching to the same phenotype for some strains but to different phenotypes for others, results of which indicate that the two cations do not always promote the same changes in underlying gene expression. The data here provide further evidence that exposure of V. vulnificus to select cations results in phenotypic changes that impact both virulence capacity and ecology of the organism.